The Influence of Training and Job Promotion on Employee Performance at PT. XYZ - Rahmadiani, Rani; Hasanuddin Hasanuddin; Jumawan Jumawan; Fauzi, Achmad; Setyawati, Novita Wahyu (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This research was conducted to analyze the effect of Training and Promotion on the Performance of Employees at PT. XYZ. This research uses a quantitative method with a sample size of 60 employees and employs a census sampling technique. The data collection technique used a questionnaire with several statements measured using a Likert Scale. Data analysis was conducted using the Structural Equation Modeling (SEM) method through SmartPLS 4.1 software. The research results show that partially, Training (X1) and Job Promotion (X2) have a significant positive effect on (Y) Employee Performance.